Combination Antiretroviral Therapy Is Associated With Reduction in Liver Fibrosis Scores in HIV-1-Infected Subjects. Issue 5 (February 2016) - Li, Yijia; Xie, Jing; Han, Yang; Wang, Huanling; Lv, Wei; Guo, Fuping; Qiu, Zhifeng; Li, Yanling; Du, Shanshan; Song, Xiaojing; Zhu, Ting; Thio, Chloe L.; et al.
Abstract : Abstract: HIV increases the risk of liver disease as do two common coinfections, hepatitis B and C viruses (HBV and HCV). However, whether combination antiretroviral therapy (cART) reverses or exacerbates hepatic fibrosis remains unclear. This was an observational retrospective study. cART-naïve HIV-infected subjects without a history of substance abuse (including alcohol) had liver disease stage determined by aspartate aminotransferase-to-platelet ratio indices (APRIs) and fibrosis-4 (FIB-4) before and 24 and 48 weeks after cART. All the data were retrieved from previously established cohorts. Values before and after cART were compared using Wilcoxon test for paired samples. Regression analyses were used to determine factors associated with moderate-to-severe liver disease. Of the 1105 HIV-infected subjects, 120 were HBV coinfected and 64 were HCV coinfected. About 20% of HIV monoinfected participants had APRI and FIB-4 scores consistent with moderate-to-significant fibrosis compared to ∼36% of HIV–HBV coinfected and 67% to 77% of HIV–HCV coinfected participants. In adjusted analyses compared with HIV monoinfection, HBV coinfection was associated with 1.18-fold higher APRI ( P < 0.001) and a 1.12-fold higher FIB-4 ( P = 0.007) prior to cART; while HCV coinfection was associated with 1.94-fold higher APRI ( P < 0.001) and a 1.43-fold higher FIB-4 ( P < 0.001). After 48 weeks of cART, both fibrosis scores decreased in all subjects; however, HCV coinfection was still associated with higher fibrosis scores at week 48 compared to HIV monoinfection. cART was associated with improvement in hepatic fibrosis scores in the majority of HIV-hepatitis coinfected and HIV-monoinfected Chinese participants. Abstract : Supplemental Digital Content is available in the text